¨La falta de atención de los padres, en el desarrollo de la identidad y autonomía social de los estudiantes del primer grado, de educación básica de la institución educativa “Jorge Isaac cabezas”, Langos, cantón guano, provincia de Chimborazo en el periodo académico 2015-2016¨ - Parra Molina, María Fernanda (2017)
The present research on “Lack of attention parents, in the development of the identity and social autonomy of students of first year of Basic Education at “Jorge Issac Cabezas”, education center, in Langos, Guano County, in Chimborazo Province 2015-2016 Academic Term” is a document that presents the problematics of the development of the identity and autonomy, considering the importance of the family environment that is the indispensable base of a social and autonomous suitable growth. The lack of family attention can provoke deep hurts in the children, since they restrict the psychological, social and autonomous growth. We initiate the work with the exposition(approach) of the problem, aim, variables and determining instruments for the compilation of the information; which was tabulated, processed and analyzed by the percentage method, sustained by the Theoretical Frame and raising conclusions and recommendations. In the Theoretical Frame there are described topics related to the problems caused by the lack of attention of the parents in the identity and autonomy in the integral development of the children. Inside the used Methodology it were considered to be the Descriptive, Explanatory type of investigation, the independent and dependent determination on variables. The Population of this study is composed by students (between 5 and 6 years), registered in the first Year of BGE "Jorge Isacc Cabezas" Education Center in Langos, Guano county, along this investigation one tried to approach the importance of the topic related to the lack of attention of the parents in the development of the identity and autonomy, across time-sharing with the children and their distribution throughout the day; observing the influence of the lack of attention of the parents, the same one that causes failings in the development of the identity and autonomy of the children and girls.